The effectiveness of biomechanical technology-based sports training models in improving elementary school students' motor skills - Timba, Frederiksen Novenrius Sini; Chandra, Conchita Junita; Rawe, Aschari Senjahari; Mbari, Maria Angelina Fransiska (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
Fundamental motor skills are an essential foundation for the holistic development of elementary school students, influencing their health, self-confidence, and academic success. This study aims to develop and test the effectiveness of a Biomechanics-Integrated Technology-Based Sports Training Model (VAB-F) to improve elementary school students' long jump motor skills. This study employed a multidisciplinary design, utilising mixed methods and a sequential explanatory approach, with a quantitative stage in the form of a quasi-experiment (pre-test post-test control group design) involving 60 fifth-grade students from SDK Magepanda. The sample was randomly divided into an experimental group (n = 30) and a control group (n = 30). Motor skills were assessed using a validated long jump technique quality assessment rubric, which was supplemented with biomechanical analysis through the Kinovea application and a Wearable Activity Tracker. The qualitative stage consisted of interviews with 6 students and 2 teachers. The results showed that the experimental group experienced a statistically significant increase in skill scores (an average increase of 29.70 points) compared to the control group (an average increase of 9.60 points), with the t-test results indicating a highly significant difference (t(58) = 15.23, p < 0.05). The qualitative results showed that the visual feedback technology encouraged independence, motivation, and intuition of student movement efficiency. It was concluded that the VAB-F training model was significantly more effective than traditional methods in improving the long jump motor skills of elementary school students.